2019
DOI: 10.1016/j.bandl.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Are you really cursing? Neural processing of taboo words in native and foreign language

Abstract: The use of socially opprobrious words (taboo words) is a cross-cultural phenomenon occurring between individuals from almost all social extractions. The neurocognitive correlates of using taboo words in the native language (L1) as compared to their use in a second (L2) language are largely unknown. We used fMRI to investigate the processing of taboo and non-taboo stimuli in monolinguals (Experiment 1) and highly proficient bilinguals (Experiment 2) engaged in lexical decision tasks. We report that for L1 socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 49 publications
5
35
1
Order By: Relevance
“…For example, bilinguals have shown to be more emotional when responding to moral dilemmas in their native compared to their foreign language (e.g., Costa, Foucart, Hayakawa, Aparici, Apesteguia, Heafner & Keysar, 2014; Geipel, Hadjichristidis & Surian, 2015a, 2015b; Cipolletti, McFarlane & Weissglass, 2016). This finding is in line with the work that has revealed that bilinguals also experience weaker emotional activation upon hearing emotional words in their second than their native language (e.g., Chen, Lin, Chen, Lu & Guo, 2015; Harris, Aycicegi & Gleason, 2003; Sulpizio, Toti, Del Maschio, Costa, Fedeli, Job & Abutalebi, 2019). The current study reports which circumstances may affect this so-called F oreign- L anguage effect , giving insight into the flexibility of moral decision making.…”
Section: Introductionsupporting
confidence: 90%
“…For example, bilinguals have shown to be more emotional when responding to moral dilemmas in their native compared to their foreign language (e.g., Costa, Foucart, Hayakawa, Aparici, Apesteguia, Heafner & Keysar, 2014; Geipel, Hadjichristidis & Surian, 2015a, 2015b; Cipolletti, McFarlane & Weissglass, 2016). This finding is in line with the work that has revealed that bilinguals also experience weaker emotional activation upon hearing emotional words in their second than their native language (e.g., Chen, Lin, Chen, Lu & Guo, 2015; Harris, Aycicegi & Gleason, 2003; Sulpizio, Toti, Del Maschio, Costa, Fedeli, Job & Abutalebi, 2019). The current study reports which circumstances may affect this so-called F oreign- L anguage effect , giving insight into the flexibility of moral decision making.…”
Section: Introductionsupporting
confidence: 90%
“…The comparative result for the mean and leading hedge, the null effect of list composition, and the modulation of the N170 suggest that once available, emotional information-an inherent semantic feature of the stimulus-percolates into the early stages of word recognition and affects orthographic processing. Converging evidence for this interpretation comes from a recent fMRI study by Sulpizio et al (2019), who ran a lexical decision experiment with taboo and neutral words. The authors found that, compared to neutral words, taboo words were associated to a weaker involvement of the left and right fusiform gyrus, a structure specialized in the extraction and storing of abstract patterns from visual(-orthographic) information.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the language being among our privileged means to communicate emotional content, the research on whether and how emotion modulates language processing is scanty. The interest in the relation between language and emotion has increased recently (e.g., Dhooge & Hartsuiker, 2011;Estes & Adelman, 2008;Grecucci, Sulpizio, Tommasello, Vespignani, & Job, 2019;Kousta, Vinson, & Vigliocco, 2009;Sulpizio, Grecucci, & Job, 2020;Sulpizio, Toti, Del Maschio, Costa, Fedeli, Job, & Abutalebi, 2019). The results of these studies show that emotion words differ from neutral words and that the valence of the emotion words has a role, but the directions of the effects are not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has suggested that bilinguals have different access to emotion depending on whether they use their first native language (L1) or their second foreign language (L2). Recounting a traumatic memory, saying "I love you" or reading a taboo word are all examples of processes that have been found to be less automatic and less affected by emotional activation in L2 than in L1 (Caldwell-Harris, 2014;Caldwell-Harris et al, 2013;Fan et al, 2016;Ivaz et al, 2016;Pavlenko, 2012;Sulpizio et al, 2019). This language effect influences memory too: Foreign language emotional words are recalled worse than native language ones (Baumeister et al, 2017;El-Dakhs & Altarriba, 2018Jay et al, 2008;Talmi & Moscovitch, 2004;Vidal et al, 2019).…”
Section: Fmri Evidence Reveals Emotional Biases In Bilingual Decisionmentioning
confidence: 99%